Kualitas Daging Broiler yang Dimarinasi Menggunakan Air Perasan Jeruk Sambal (Citrus microcarpa) dengan Konsentrasi dan Lama Perendaman yang Berbeda - Ardiansyah, Fajri; Lestari, Retno Budi; Purnomosidi, Marjoko (Jurnal Sains Pertanian Equator, 2020)
Sambal lime juice is one of the marinated ingredients that contain citric acid that have the function of preserving the quality of broiler meat. This research aimed to determine the quality of broiler meat marinated using sambal lime (Citrus microcarpa) juice with different concentrations and the immersion durations. The materials of this research were 24 pieces of broiler meat breasts. This research has used the factorial, completely randomized design (CRD). The first factor was the concentrations and the second factor was immersion durations of sambal lime, with the treatment combination were: 10%;10 minutes (K1L1), 10%;20 minutes (K1L2), 10%;30 minutes (K1L3), 20%;10 minutes (K2L1), 20%;20 minutes (K2L2), dan 20%;30 minutes (K2L3) with four replicated. The observed variables were the pH, protein content and water holding capacity. The results showed that the quality of broiler meat marinated using sambal lime juice, with different concentrations, did not affect all variables. However, the different immersion duration had a very significant effect on the pH value (4,67-5.47) and did not influence on protein content (21.38-22.54%) and water holding capacity (65.50-69.50%). The conclusion of this research is the best treatment of marinating using sambal lime juice on broiler meat quality is a concentration of 10% with an immersion duration of 20 minutes.